Position specific morphological characteristics of elite water polo players - Lozovina, Mislav (Array, 2009)
Abstract: The aim of the study was to determine morphological characteristics of elite water polo players. In a sample of 121 water polo players, the structure of a set of 23 morphological space variables was determined by use of factor analysis, followed by determination of differences between all pairs of playing positions in the manifest morphological space by use of Post Hoc analysis.